Negotiating Gender Roles through Social Media Cruise: A Discourse Analysis of Geh-Geh University Narratives - Udoudom, Uduak; George, Kufre; Ekanem, Idorenyin; Etifit, Samuel (Darul Yasin Al Sys, 2025)
This study explores how gender roles are being negotiated through social media cruise culture, using Geh-Geh University—a popular online platform created by Nigerian social media influencer Geh-Geh—as a case study. The core issue examined is the ideological contest between divergent gender role messages promoted by Geh-Geh and his critics, such as Saidaboj and Blessing CEO, whose opposing views reflect broader societal tensions around gender expectations among Nigerian youths. Guided by Social Identity Theory, which explains how individuals align with social groups to affirm their identities and values, the study employed qualitative discourse analysis to examine online narratives and audience interactions across platforms including TikTok, Facebook, YouTube, blogs, and Instagram. Findings show that Geh-Geh uses humor, everyday language, and relatable storytelling to encourage young men to embrace hard work, responsibility, and value women who support them. In contrast, critics like Saidaboj and Blessing CEO promote messages that endorse financial dependence on men and normalize